Perceived difficulty of various steps of manual small incision cataract surgery among trainees in rural China. (3rd March 2013) - Huang, Wenyong; Ye, Ronghua; Huang, Shengsong; Wang, Decai; Wang, Lanhua; Liu, Bin; Friedman, David S; He, Mingguang; Liu, Yizhi; Congdon, Nathan G
Abstract: Background: The perceived difficulty of steps of manual small incision cataract surgery among trainees in rural China was assessed. Design: Cohort study. Participants: Fifty‐two trainees at the end of a manual small incision cataract surgery training programme. Methods: Participants rated the difficulty of 14 surgical steps using a 5‐point scale, 1 (very easy) to 5 (very difficult). Demographic and professional information was recorded for trainees. Main Outcome Measure: Mean ratings for surgical steps. Results: Questionnaires were completed by 49 trainees (94.2%, median age 38 years, 8 [16.3%] women). Twenty six (53.1%) had performed ≤50 independent cataract surgeries prior to training. Trainees rated cortical aspiration (mean score ± standard deviation = 3.10 ± 1.14) the most difficult step, followed by wound construction (2.76 ± 1.08), nuclear prolapse into the anterior chamber (2.74 ± 1.23) and lens delivery (2.51 ± 1.08). Draping the surgical field (1.06 ± 0.242), anaesthetic block administration (1.14 ± 0.354) and thermal coagulation (1.18 ± 0.441) were rated easiest. In regression models, the score for cortical aspiration was significantly inversely associated with performing >50 independent manual small incision cataract surgery surgeries during training ( P = 0.01), but not with age, gender, years of experience in an eye department or total number of cataract surgeries performed prior to training. Conclusions: Cortical aspiration, wound construction and nuclear prolapse pose the greatest challenge for trainees learning manual small incision cataract surgery, and should receive emphasis during training. Number of cases performed is the strongest predictor of perceived difficulty of key steps.